The role of semaphorin 3A in the pathogenesis and progression of Alzheimer’s disease and other aging-related diseases: A comprehensive review - Jiayu Yuan; Rui Huang; Jianfei Nao; Xiaoyu Dong (Pharmacological Research)
Aging serves as a pivotal factor in the etiology of numerous diseases, such as Alzheimer's disease (AD), Parkinson's disease, diabetes, osteoarthritis, atherosclerosis and aging-related macular degeneration. Notably, these diseases often interact with AD through various pathways, facilitating the onset or progression of one another. Semaphorin 3 A (Sema3A), a protein that is essential for axonal guidance during neural development, has recently been identified as a novel regulator in the pathogenesis and progression of multiple aging-related diseases. This article provides a comprehensive review of the expression patterns and mechanisms of action of Sema3A in these diseases. Specifically, Sema3A influences the occurrence and development of aging-related diseases by participating in oxidative stress, inflammatory responses, apoptosis, and synaptic plasticity. Therefore, therapeutic strategies targeting Sema3A present promising avenues for delaying the progression of aging-related diseases and offer novel insights and strategies for their treatment.